Peran Kepala Sekolah sebagai Manajer dalam Meningkatkan Partisipasi Masyarakat di SD Islam Az-Zahrah - Nursamsiah Siregar (Studia Manageria, 2019)
This study aims to reveal the principal as a manager in increasing community participation, community participation in schools and the factors that support and hinder school principals as managers in increasing community participation in Islamic Az-Zahrah Elementary School in Palembang. This research includes field research, namely research by direct way to the place of research to observe and be directly involved with the object of research. This type of research is a qualitative case study research with inductive thinking logic, where this study has the characteristics that the data is stated in a reasonable state. This study uses qualitative methods, namely the methods of observation, interviews, and documentation. The results of the study are (1) school principals in increasing participation through service delegations, (2) Community participation in schools, both the community in general, and through school committees in providing advisory (advisory agencies), providing support (supporting agencies) overseeing the implementation of education in school (controlling agency) and the liaison between the school and parents of students (mediators) can be done well, (3) While the inhibiting factor in increasing community participation, especially parents, they do not have much time to participate directly in every school activity.